Homomorphism and sigma polynomials - Richard Alan Gillman (International Journal of Mathematics and Mathematical Sciences)
By establishing a connection between the sigma polynomial and the homomorphism polynomial, many of the proofs for computing the sigma polynmial are simplified, the homomorphism polynomial can be identified for several new classes of graphs, and progress can be made on identifying homomorphism polynomials.